Meningkatkan Keaktifan Dan Hasil Belajar Materi Redoks Dan Elektrokimia Melalui Model Problem Based Learning - Juliana Sri Mulyati (Jurnal Lingkar Mutu Pendidikan, 2021)
Chemistry belongs to the specialization group together with mathematics and other science subjects. For students who choose these specializations and have a lack of interest in learning chemistry subjects, there is a compulsion to study them. They will find difficulties understanding chemical concepts, especially in more complex concept such as redox and electrochemical materials. Based on the mid-semester assessment in the last two years, the average score is 57 and learning outcomes are 69% below the KKM and the average activity based on the questionnaire is below 60%. This research uses classroom action research (CAR) method which aims at improving the quality of learning chemistry. It uses two cycles. Each cycle includes the stages of planning, implementing, observing, and reflecting. It uses Problem Based Learning Model on Redox and Electrochemical materials. For the learning outcomes in cycle 1, only 18 students or 50% can achieve average score 68 and the average of students’ activeness in discussions is 60%. 31 students or 86% can get average score 84 and the activeness in discussions becomes 74% in cycle 2.